Identifying as an evidence-based social worker: the influence of attitudes, access, confidence, and education. Issue 4 (19th May 2018) - Teater, Barbra; Chonody, Jill M.
Abstract: This study explored United States-based social workers' ( N = 152) attitudes toward, access to, and confidence in engaging in evidence-based practice (EBP), the extent to which social work education prepared them to engage in EBP, and the factors that contributed to their identification as an evidence-based practitioner. Findings indicated that although practitioners had a positive attitude toward engaging in EBP, they were only moderately confident in doing so, rarely accessed evidence, and were only moderately prepared through their education. Believing that EBP should be implemented, more educational preparation, and positive attitudes contributed to greater identification as an evidence-based practitioner, areas that social work and continuing education should further support to enhance social workers' EBP skills.